Analisis Sistem Informasi Akuntansi Menggunakan Aplikasi JSmart: (Studi Kasus pada Perusahaan Daerah Air Minum (PDAM) Kota Mojokerto) - Saputri Dwi Fitriani; Nur Ainiyah; Nurdiana Fitri Isnaini (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Accounting information systems are very important for companies because they can simplify operational activities and reduce uncertainty in decision making. This research aims to determine the use of the Jsmart application in the accounting information system at PDAM Mojokerto City. This research uses primary and secondary data with qualitative descriptive methods through observation, interviews and documentation. The research results show that the JSmart application used by PDAM Kota Mojokerto significantly increases accuracy, efficiency and transparency in calculating and determining billing costs. The application automates cost calculations, reduces manual errors and speeds up processes, thereby supporting strategic decision making and increasing customer satisfaction. JSmart has also proven effective in presenting accurate financial information and facilitating financial data analysis.